Formation Of a Photosynthetic Apparatus in Phaseolus Vulgaris L. Depending on The Application of Gibberillin and Succinic Acid Growth Stimulators - Kim Veronika Vladimirovna; Narimanov Abdujalil Abdusamatovich (Zien Journals, 2021)
This article describes that using various growth stimulantors, the largest leaf area and photosynthetic potential are formed. The highest indicators of leaf area were observed in the variants gibberillin and succinic acid - (40.2 and 39.3 m2 / m2). At the same time, the photosynthetic potential (FP) exceeded the control variant by 290.9 and 160.1 thousand m2 /ha/day. It was revealed that, depending on the different methods of seed treatment in the beans of vegetable beans, the content of protein, fat, total sugar, vitamin C, starch and nitrates was different.
Keywords: vegetable beans; seed treatmen; growth stimulators; leaf area